Modern trends and problematic issues in consumer lending in Ukraine - Оніщенко, Ольга Вікторівна; Степанова, Юлія Олегівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The article analyzes the main problem areas of consumer credit and sets out key areas to improve credit conditions of the population in Ukraine The article analyzes the current state of consumer lending in Ukraine, identifies the main problem areas of consumer credit, which includes currency instability, the risk of loan default, decrease in the number of potential borrowers and other problems referred in the article, including their solutions: improve the quality of service and customer advice, conducting training sessions for staff of banks, improve financial literacy of population and other solutions. The methodical approach to make the right decisions on the problems of ensuring individuals’ consumer loans. The basic factors influencing the development of consumer lending. Ukrainian complaining of lack of funds, make out a loan, if you pay for the order which give more than take. There is a sure way to double your income - to get rid of loans and credit cards. The problem of our people is that we are not looking for many ways to profit, we think, how we quickly get the goods to be like everyone else. Thus, having issued credit we give the money to good shops and pay interest on bank services.